2018
DOI: 10.1186/s12891-018-2283-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-infection rates and clinical outcomes following arthrodesis with intramedullary nail and external fixator for infected knee prosthesis: a systematic review and meta-analysis.

Abstract: BackgroundKnee arthrodesis with intramedullary (IM) nail or external fixator (EF) is the most reliable therapeutic option to achieve definitive infection control in patients with septic failure of total knee arthroplasty (TKA). The first aim of this study was to compare re-infection rates following knee arthrodesis for periprosthetic joint infection (PJI) with IM nail or EF. The second aim was to compare rates of radiographic union, complication, and re-operation as well as clinical outcomes.MethodsA systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
(67 reference statements)
1
18
1
4
Order By: Relevance
“…In 2018 Balato et al were able to show in a systematic review and metaanalysis of 26 publications that in IMA the rate of reinfection and persistence of infection was 13.3% (422 cases studied), while other studies reported rates between 0% (19 investigated cases in Letartre et al 2009) and 50% (26 cases studied byRöhneretal. 2015) [32][33][34]. In contrast, our study showed a proven rate of persistent infections or reinfections of 33% (18 cases studied).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…In 2018 Balato et al were able to show in a systematic review and metaanalysis of 26 publications that in IMA the rate of reinfection and persistence of infection was 13.3% (422 cases studied), while other studies reported rates between 0% (19 investigated cases in Letartre et al 2009) and 50% (26 cases studied byRöhneretal. 2015) [32][33][34]. In contrast, our study showed a proven rate of persistent infections or reinfections of 33% (18 cases studied).…”
Section: Discussioncontrasting
confidence: 61%
“…Persistent infections of the knee joint represents a major therapeutic challenge, in which, after the failure of joint-preserving therapeutic attempts, an arthrodesis of the affected joint has proven to be one of the most reliable surgical treatments for definitive healing of infection while preserving the extremity [15]. The procedures frequently described and compared in the literature are intramedullary nail arthrodesis and EMA using an external fixator [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative to conventional static immobilization, intramedullary (IM) nails have been increasingly utilized to treat infections of the knee. [18][19][20] Purported benefits of IM nails include the delivery of high concentrations of antibiotics, improved stability, and prevention of further bone loss. 21,22 Additionally, this procedure helps preserve the limb, allowing patients to be functionally independent while maintaining a normally aligned knee that patients can ambulate on soon after surgery.…”
mentioning
confidence: 99%